E-procurement espousal and assessment framework: A case-based study of Indian automobile companies. (1st March 2018) - Jain, Mukul; Abidi, Naseem; Bandyopadhayay, Asit
The Indian automobile industry is one of the fastest growing industries in the country. Considering the importance of e-procurement in automobile industry, many researchers have developed various models that help organizations to adopt e-procurement successfully. The implementation of e-procurement is divided into three phases: pre-espousal, espousal and assessment. These three phases are very crucial and important for the success of any e-procurement system. Different frameworks have been suggested for the espousal and assessment of e-procurement. In this article the authors develop a composite framework that integrates all the three phases of e-procurement system in the Indian automobile industry with the help of an integrative literature review, three case studies and an experience survey. However, this is purely a conceptual framework that requires validation before implementation.